A política republicana em Santo Ângelo (1900-1924) : a experiência política do Coronel Bráulio Oliveira - Mariano, Viviane Letícia Glienke (2007)
This Master´s dissertation called The republican politics in Santo Ângelo: Colonel Bráulio Oliveira´s political experience brings along the discussion on the regional political history. It approaches the period between 1900 and 1924, when Bráulio Oliveira was consolidated unipersonal leader of the local politics and the republican party in Rio Grande do Sul. Considering the political history in Rio Grande do Sul as the background to this study, this subject covers significative changes in Santo Ângelo´s society. The same way the maintenance of a political elite and the appearance of the dissident groups inside PRR, led by Damaso Gomes de Castro. These two leaders give rise to the two trends inside the party: braulistas and damistas . Inserted in this context, in 1916, Álvaro Silveira takes the stewardship power. Because of the renouncement of the steward, Major Quinzote takes the power and concludes these 4 years. In 1920, Bráulio is once again elected steward, but his government is not the way it was beforehands. The society had changed and new leaders showed up, members of this dissidence that leads to the 1923 Revolution